Implikasi Pola Asuh Orang Tua Terhadap Pembentukan Sikap Kemandirian Santri di Pesantren - Yanto Yanto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Islamic boarding schools do not only have the task of teaching religious knowledge. Apart from that, Islamic boarding schools also have an important role in giving birth to the formation of students who are independent in facing all the needs and challenges of life in the future. The independence of students in Islamic boarding schools is closely related to the parenting style of parents in the family environment. Children who are raised with a certain parenting style will have implications for independence while in the Islamic boarding school environment. One indicator of student independence is the existence of life skills in students in meeting their daily needs at the Islamic boarding school. The aim of the research is to describe the implications of parenting patterns for the formation of students' independent attitudes in Islamic boarding schools. The research was conducted qualitatively through literature study. Data collection techniques with documentation and data management with data reduction and presentation. The results of the research show: (1) people's parenting patterns have implications for the independence of students. Students who are raised with a democratic parenting style tend to adapt more easily to the Islamic boarding school environment and live independently and easily build communication and interaction with other students. (2) efforts to foster the independence of students at Islamic boarding school XXX are one of the duties of Islamic boarding school administrators and room heads/block heads. (3) to foster independence in students can be done by parents not visiting their children at the Islamic boarding school too often because this will slow down the growth of an independent attitude in the child. (4) parents need to have the courage to allow their children to fulfill their needs at the Islamic boarding school.